Tracking the Progression of Osteolytic and Osteosclerotic Lesions in Mice Using Serial In Vivo μCT: Applications to the Assessment of Bisphosphonate Treatment Efficacy. (17th November 2017) - Campbell, Graeme M; Tower, Robert J; Damm, Timo; Kneissl, Philipp; Rambow, Anna C; Schem, Christian; Tiwari, Sanjay; Glüer, Claus C
ABSTRACT: The metastasis of tumor cells to bone can lead to osteolytic and osteosclerotic lesions, which cause severe, highly‐localized bone destruction and abnormal bone apposition, respectively. Accurate quantification of lesion progression is critical to understand underlying mechanisms and assess treatment efficacy; however, standard structural parameters may be insensitive to local changes. We developed methods to quantify osteolytic and osteosclerotic lesions using micro–computed tomography (μCT) within in vivo mouse datasets. Two Balb/c nude datasets were used: (i) bone‐homing MDA‐MB‐231 (osteolytic) cells injected into the left ventricle, treatment with alendronate or vehicle, and weekly μCT (proximal tibia) for 4 weeks, and (ii) MCF7 (osteosclerotic) cells injected into the right tibia and weekly μCT over 12 weeks. After registering images to baseline, osteolytic lesion volume was determined by summing all baseline bone voxels at distances greater than a threshold (150 μm) from the nearest follow‐up. Osteosclerotic lesions were determined by measuring the distance from each follow‐up surface voxel to the nearest baseline surface and calculating the standard deviation of distance values (SDDT) of the surrounding voxels. Bone mineral density (BMD), bone volume density (BV/TV), and separation (Sp) were determined for comparison. Osteolytic lesions were observed 1 week after tumor cell injection; however, no corresponding BV/TV losses or Sp increases were observed, indicating that standard parameters were unable to detect early metastatic changes. Lesion volume was smaller in the alendronate versus control group (15.0%, p  = 0.004 and 18.6%, p  = 0.002 of control lesion volume at weeks 3 and 4, respectively). In the osteosclerotic dataset, increased SDDT was observed following injection, providing a potential new measure of osteosclerotic bone apposition. These data show that quantification of local structural change with serial μCT may overcome the limitations of standard mineral and microstructural parameters, and successfully separates metastatic and normal bone turnover. © 2017 American Society for Bone and Mineral Research.